2000
DOI: 10.1007/s004240000354
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of fetal and adult acetylcholine receptors by Ca2+ and Mg2+ at developing mouse end-plates

Abstract: It has long been known that extracellular Ca2+ and Mg2+ modulate synaptic transmission at the neuromuscular junction, acting both pre- and post-synaptically. Relevant questions concerning the modulation of acetylcholine (ACh) receptors (AChRs) are however still open: are the fetal (gamma-AChR) and adult (epsilon-AChR) receptors modulated differently? Does the ACh concentration influence the effect of divalent cations? Is the effect on channel open duration dependent on type and concentration of divalent cation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Thus, in this new co-culture model, nerve-muscle The development of mature neuromuscular junctions in this co-culture system is also supported by the electrophysiological characterization of AChRs. Indeed, single-channel currents recorded from non-innervated myotube cultures had characteristics (small single-channel conductance, long mean open time) consistent with expression of AChRs of the embryonic form [9,10,16,25,29]. As AChR activity with similar characteristics was observed in myotubes from 10-day-old co-cultures, we conclude that fibers from young co-cultures express the fetal form of AChR.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Thus, in this new co-culture model, nerve-muscle The development of mature neuromuscular junctions in this co-culture system is also supported by the electrophysiological characterization of AChRs. Indeed, single-channel currents recorded from non-innervated myotube cultures had characteristics (small single-channel conductance, long mean open time) consistent with expression of AChRs of the embryonic form [9,10,16,25,29]. As AChR activity with similar characteristics was observed in myotubes from 10-day-old co-cultures, we conclude that fibers from young co-cultures express the fetal form of AChR.…”
Section: Discussionsupporting
confidence: 51%
“…4B), the single-channel slope conductance was 33.5€0.6 pS (n=20). This value is typical of the embryonic type of AChR channel containing the g subunit [4,9,10,16,25,28]. The extrapolated zero-current potential was 72.1€2.6 mV (Fig.…”
Section: Recordings From Non-innervated Myotube Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Krendal [7] suggested that magnesium sulfate has a pre-synaptic effect by inhibiting acetylcholine release at motor nerve terminals, effects that may be responsible for the interaction with vecuronium. Furthermore, some studies have shown that increasing extracellular magnesium reduces the size of acetylcholine-evoked responses and the single-channel conductance of nicotinic acetylcholine receptors at the mouse end-plate [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Significant fluctuations in [Ca 2ϩ ] o and [Mg 2ϩ ] o may occur in association with normal brain activity (Massimini and Amzica, 2001), as well as with a variety of pathological phenomena including ischemia, hypoglycemia, and seizures (Harris and Symon, 1984;Silver and Erecinska, 1990;Kristian et al, 1993;Altura et al, 1997). The effects of extracellular divalent cations may be mediated by multiple mechanisms, including modulation of Ca 2ϩ , K ϩ , and Na ϩ channels (Delpiano and Altura, 1996;Su et al, 2001;Yamaoka et al, 2002), cyclic nucleotide-gated channels (Colamartino et al, 1991;Frings et al, 2000;Lee et al, 2001), and ligand-gated channels (Grassi and Degasperi, 2000;Negulyaev and Markwardt, 2000;Arvanian and Mendell, 2001), as well as by direct activation of G-protein-coupled receptors (Riccardi, 1999;Brown, 2000). Until recently, attention has been focused primarily on the effects of extracellular divalent cations on neuronal signaling.…”
Section: Introductionmentioning
confidence: 99%